2020
DOI: 10.3389/fnut.2020.00139
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of Fat and Carbohydrate Metabolism to Glucose Homeostasis in Childhood Change With Age and Puberty: A 12-Years Cohort Study (EARLYBIRD 77)

Abstract: Puberty—a period when susceptibility to the onset of Type 2 diabetes (T2D) increases—is marked with profound physiological and metabolic changes. In the EarlyBird cohort, children who developed impaired fasting glycemia in adolescence already exhibited higher fasting blood glucose at 5 years of age, independent of their body mass index (BMI), suggesting that pubertal factors may modify existing predisposition. Understanding how the physiological changes during childhood influence glucose homeostasis and how th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 58 publications
(83 reference statements)
0
6
0
Order By: Relevance
“…This study examined the association between BCAAs and different sleep characteristics in a large, population-derived sample of Although BCAAs were not associated with adult sleep, significant associations were observed for children's sleep duration, timing, and self-reported trouble sleeping, even after adjusting for sex, puberty stage, SEP, and BMI z-score. Biological processes related to growth and development (puberty) may explain why different associations are observed for children (Cominetti et al, 2020;Terasawa, 2005). In particular, puberty has been shown to involve changes in amino acid metabolism, with complex patterns specifically observed for BCAAs (Cominetti et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study examined the association between BCAAs and different sleep characteristics in a large, population-derived sample of Although BCAAs were not associated with adult sleep, significant associations were observed for children's sleep duration, timing, and self-reported trouble sleeping, even after adjusting for sex, puberty stage, SEP, and BMI z-score. Biological processes related to growth and development (puberty) may explain why different associations are observed for children (Cominetti et al, 2020;Terasawa, 2005). In particular, puberty has been shown to involve changes in amino acid metabolism, with complex patterns specifically observed for BCAAs (Cominetti et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…These variables were selected as covariates as they have been associated with both sleep and metabolomics profiles, particularly BCAAs (Dollman et al, 2007 ; Felden et al, 2015 ; Jarrin et al, 2014 ; Ohayon et al, 2004 ; Olds et al, 2010 ). For children, pubertal stage rather than age was selected as a covariate as the children examined in this study were within a narrow age range (11–12 years) and since complex changes in amino acid metabolism have been observed during puberty (Cominetti et al, 2020 ). Puberty was assessed using the Puberty Development Scale, a validated self‐report questionnaire that consists of five Likert scale questions (Chan et al, 2010 ; Petersen et al, 1988 ).…”
Section: Methodsmentioning
confidence: 99%
“…Although we did not classify this study population into prepubertal, pubertal and postpubertal groups, these different stages of development have been shown to be indicative of age and hormone production; for example, growth hormone is involved in glycogen metabolism (i.e., glycogenolysis and gluconeogenesis) and lipid metabolism throughout childhood. In addition, it has been reported that at prepubertal ages, there is a greater preferential oxidation of fat over carbohydrates during exercise, in contrast to pubertal and postpubertal subjects ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…Differences between men and women are biology-linked and caused by differences in sex chromosomes, hormones, and gene expression of sex-specific autosomes, which can each have effects on organ systems ( 74 ). Especially during adolescence when the fuel economy shifts away from fatty acid composition and ketogenesis toward carbohydrate oxidation, there is reduced metabolic flexibility making puberty a vulnerable period for changes in body composition ( 75 ). Women generally have lowered insulin sensitivity ( 75 77 ) (as was also observed in this present study) or increased impaired glucose tolerance than do males ( 74 ), which may increase their susceptibility or sensitivity to dietary influences.…”
Section: Discussionmentioning
confidence: 99%